Modeling of overcurrent protective relay response time to electrical transients in power systems - Canseco, Roy Vincent Luna
Protection systems have an important role to play in a field that commands constant improvement in efficiency and service. Relays are central to power system protection; thus, understanding and preventing relay miss-operation is important. In this paper, a solution to relay miss-operation is presented. A methodology of statistical nature using overcurrent relay modeling techniques such as direct data storage, curve-fitting, and parameter estimation is proposed. Regression models were developed to model the characteristics of overcurrent protective relays in the presence of a drift in frequency and in the presence of distortion. The objective is to offer an economic and efficient strategy for improving power system protection through better relay miss-operation investigation. The models created were verified through comparison with manufacturer's curves and empirical data from previous research. The results were represented in 3D and color density plots to provide greater insight in investigating relay miss-operations.